The city as a project. - (:unkn) unknown (Ruby Press, 2014)
This book represents an attempt to understand the city as an act - or project - that defines a political intentionality, thus establishing a precondition for engagement with the city's complex nature. The book attempts a sort of historical survey of the idea of the project -and, more specifically, the architectural project - for the city. Far from being comprehensive, this survey aims to define a possible direction for architectural research that is neither strictly scholarly or academic, nor a journalistic analysis of the latest trends in the contemporary city. The book is introduced by a chapter that develops the idea of the architectural project for the city and is followed by eight essays organized in five thematic sections. Starting from before the project - that is, the city before the invention of this category - and ending with the collapse of the project during the urbanization of the last century, the book attempts, in each chapter, to show the strategie role played by architectural form in shaping ideas of the city.
Keywords: Stadtgeschichte; Stadtforschung; Architekturtheorie; Architektur; Stadttheorie